Effects of soil heavy metal pollution on microbial activities and community diversity in different land use types in mining areas - Zhao, Xingqing; Sun, Yu; Huang, Jian; Wang, Hui; Tang, Ding (Environmental science and pollution research international, 2020)
Microbial activities and community structures play crucial roles in the soil environment and can be served as effective indicators to assess the ecological influence of heavy metal pollution in soil. This article selected soil samples from five land use types (mining area, mineral processing area, heap mining area, tailing area, and vegetable area) in the Shizishan mining area in Tongling, Anhui Province, China. The physicochemical properties, pollution characteristics, enzyme activities (catalase, urease, alkaline phosphatase, neutral phosphatase, cellulase, and sucrase), microbial biomass carbon (MBC), basal respiration (SBR), and metabolic entropy (qCO 2 ) in soil were determined and compared, and the relationship between environmental factors and the microbial activities and community diversity was analyzed. The results showed that, according to the Nemerow’s Pollution Index ( P N ), the values were the heap mining area (24.47) > mineral processing area (12.55) > mining area (9.81) > tailings area (6.02) > vegetable area (4.51). With the increase of heavy metal contamination in the sampling area, the six enzyme activities, MBC and SBR decreased, but the qCO 2 increased. Principal coordinate analysis (PCoA) and canonical correlation analysis (CCA) showed that the land use types, soil moisture content (MC), heavy metal content, pH, MBC, SBR, and qCO 2 were significantly affected by the microbial community. The most dominant phyla were Proteobacteria (34.73%), Bacteroidetes (9.25%), Acidobacteria (8.99%), and Chloroflexi (8.68%) at the phylum (0.01) level by a total of 18 phyla. It was also found that Firmicutes and Phormidium were more tolerant to heavy metals. These results contributed to an insight into key environmental variables shaping the microbial activities, community structure, and diversity under various land use types in mining area.